2014
DOI: 10.1017/s002237781400083x
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics and magnetic induction in the von-Kármán plasma experiment

Abstract: The von-Kármán plasma experiment is a novel versatile experimental device designed to explore the dynamics of basic magnetic induction processes and the dynamics of flows driven in weakly magnetized plasmas. A high-density plasma column (10 16 -10 19 particles. m −3 ) is created by two radio-frequency plasma sources located at each end of a 1 m long linear device. Flows are driven through J × B azimuthal torques created from independently controlled emissive cathodes. The device has been designed such that mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…In many experiments, two-faced Mach probes or similar devices are used for this purpose. 3,[26][27][28][29] The Mach probe is a two-side planar or cylindrical probe where the IVcurve of each side is measured. In presence of non-zero plasma flux in direction normal to the probe surface, the ion saturation currents are different for the two sides of the probe indicating a non-zero ion drift.…”
Section: Experimental Validation Of a Plasma Flow In Presence Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In many experiments, two-faced Mach probes or similar devices are used for this purpose. 3,[26][27][28][29] The Mach probe is a two-side planar or cylindrical probe where the IVcurve of each side is measured. In presence of non-zero plasma flux in direction normal to the probe surface, the ion saturation currents are different for the two sides of the probe indicating a non-zero ion drift.…”
Section: Experimental Validation Of a Plasma Flow In Presence Ofmentioning
confidence: 99%
“…[5][6][7][8] For example, a recent von-Karman flowing plasma experiments aims to explore the dynamics of basic induction processes in order to better understanding the magnetic properties of astrophysical bodies (including Earth) and interaction of the solar wind with the Earth's magnetosphere. 3,4 Another interesting example is laser-plasma accelerators recently proposed as the next revolutionary generation of particle accelerators. 1,2 These devices have great prospective in high-energy physics as very compact quasi-monoenergetic sources of relativistic particles.…”
mentioning
confidence: 99%
“…1 and described in details in Ref. 15. It consists of a cylindrical magnetized plasma device in which the plasma production is achieved by a 13.56 MHz radio-frequency (RF) power generator (up to 1.4 kW) coupled to a 3-turn antenna through a L-type matching network.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…Besides being of astrophysical (origin of observed fields) and fundamental (what happens?) physical interest, it is likely soon to be attacked not just theoretically, but also experimentally, with the advent of laboratory experiments aiming to reproduce the plasma dynamo process (Spence et al 2009;Meinecke et al 2014Meinecke et al , 2015Plihon et al 2015;Forest et al 2015). The first demonstration of this process in a 3D kinetic numerical simulation by Rincon et al (2016) has indeed confirmed the ubiquitous appearance of mirror and firehose fluctuations, although a detailed investigation of the full multiscale problem remains computationally too intensive to be affordable.…”
Section: Introductionmentioning
confidence: 99%